2006
DOI: 10.1017/s0952523806233017
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical assessment of magno- and parvocellular function in schizophrenia

Abstract: Recently developed psychophysical techniques permit the biasing of the processing of the stimulus by early visual channels so that responses reflect characteristics of either magno- or parvocellular pathways (Pokorny & Smith, 1997). We used such techniques to test psychophysically whether the global magnocellular dysfunction reported in schizophrenia also affects early processes. Seven schizophrenic patients and 19 normal controls participated. The task was a four-alternative forced-choice luminance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Thus, our results suggest that these subcortical and cortical mechanisms are relatively intact in SZ. A previous study found abnormal luminance discriminations in SZ (Delord et al, 2006). This result, however, is in contrast to normal luminance matching in the no-context control condition reported here.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, our results suggest that these subcortical and cortical mechanisms are relatively intact in SZ. A previous study found abnormal luminance discriminations in SZ (Delord et al, 2006). This result, however, is in contrast to normal luminance matching in the no-context control condition reported here.…”
Section: Discussionmentioning
confidence: 83%
“…It remains an open question whether these visual deficits are restricted to patients with negative symptoms (e.g., Slaghuis, 1998) and to certain stimuli, such as low spatial frequency gratings (Kéri et al, 2004). Delord et al (2006) found that contrast detection thresholds of schizophrenic patients were significantly poorer than those of controls for all frequencies, arguing rather for a general visual deficit. Patients show also strongly deteriorated performance for high contrast stimuli when these stimuli are fragmented, i.e., where only parts of the contour of an object are visible.…”
Section: Discussionmentioning
confidence: 97%
“…Various studies assert that visual deficits in schizophrenia patients are related to the parvocellular pathway or are related to the interaction between the magnocellular and parvocellular pathways [61, 64]. Table 2 shows some of comparative studies of magnocellular and parvocellular pathway in schizophrenia.…”
Section: Dopamine and Glutamine Rolementioning
confidence: 99%